Improving students’ reading comprehension of narrative text through question answer relationship strategy - Sherly Nanda Oktavia; Ema Butsi Prihastari; Yuyun Yuniarti (Journal of Advanced Multidisciplinary Research, 2025)
This classroom action research (CAR) examined how the Question–Answer Relationship (QAR) strategy supported eighth-grade students’ reading comprehension of narrative texts at SMP Negeri 2 Surakarta. The study addressed students’ difficulties with identifying narrative elements and answering inferential questions in an EFL context. Two CAR cycles were implemented through collaborative planning, action, observation, and reflection with the classroom teacher. Data were generated from reading comprehension tests, classroom observations, and teacher interviews. The findings indicate a consistent improvement in students’ comprehension performance across cycles, accompanied by increased engagement and strategic reading behavior. Qualitative evidence shows that students became more aware of question types and more confident in locating textual evidence and making inferences. Rather than claiming causal effectiveness, this study demonstrates that QAR functioned as a pedagogically useful strategy within a reflective CAR process. The study offers practical insights for EFL teachers seeking to scaffold students’ literal and inferential comprehension of narrative texts.